1989
DOI: 10.1021/j100354a021
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic oxidation of sulfur dioxide in aqueous suspensions of .alpha.-iron oxide (Fe2O3)

Abstract: The kinetics and mechanism of the photoassisted autoxidation of S(IV) in aqueous colloidal suspensions of a-Fe203 have been studied over the pH range of 2-10.5. Similar kinetic behavior toward S(IV) was observed for colloidal suspensions of Ti02. Quantum yields, , ranged from 0.08 to 0.3 with a maximum yield found at pH 5.7. Upon band-gap illumination conduction-band electrons and valence-band holes are separated; the trapped electrons are transferred either to surface bound dioxygen or to Fe(IlI) sites on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(165 citation statements)
references
References 3 publications
6
157
0
2
Order By: Relevance
“…Catalytic activity does not significantly change when the solid phase is filtered out of the leachate. This shows aqueous oxidation dominates over any surface effects of particles in the solution (Cohen et al, 1981;Rani et al, 1992), although, when aqueous iron and titanium oxide suspensions are irradiated, sulfate quantum yields 1 have been observed due to desorption of ·SO − 3 and initiation of a radical chain reaction (Hong et al, 1987;Faust et al, 1989).…”
mentioning
confidence: 99%
“…Catalytic activity does not significantly change when the solid phase is filtered out of the leachate. This shows aqueous oxidation dominates over any surface effects of particles in the solution (Cohen et al, 1981;Rani et al, 1992), although, when aqueous iron and titanium oxide suspensions are irradiated, sulfate quantum yields 1 have been observed due to desorption of ·SO − 3 and initiation of a radical chain reaction (Hong et al, 1987;Faust et al, 1989).…”
mentioning
confidence: 99%
“…Na reação catalisada por Fe(III), Kraft 103 encontrou uma maior quantidade de ditionato, para a reação conduzida na presença de oxigênio do que na ausência. Já Faust e col. 104 e Grgic e col. 12 não encontraram a presença de ditionato para a reação catalisada por Fe(III) em presença de ar. Brandt De acordo com Veprek-Siska e col. 106 , a reatividade do complexo metal-sulfito formado na etapa inicial do processo, é o principal fator que influencia os produtos da reação.…”
Section: -(99)unclassified
“…Several studies have already found that using size-quantized semiconductors can enhance photoefficiencies [80][81][82][83][84], although other works showed that photoactivities of size-quantized semiconductors decreased compared with their bulk-phase counterparts [81,85]. Such phenomenon should be attributed to the competition relationship between the positive effects of increased potential on quantum yields and the unfavourable surface speciation and surface defects formed during the preparation processes of semiconductor particles [86][87][88]. prepared [89][90][91][92].…”
Section: Introductionmentioning
confidence: 99%